2016
DOI: 10.1097/md.0000000000005489
|View full text |Cite
|
Sign up to set email alerts
|

Association of vagus nerve severance and decreased risk of subsequent type 2 diabetes in peptic ulcer patients

Abstract: Vagus nerve may play a role in serum glucose modulation. The complicated peptic ulcer patients (with perforation or/and bleeding) who received surgical procedures with or without vagotomy provided 2 patient populations for studying the impact of vagus nerve integrity. We assessed the risk of developing type 2 diabetes in peptic ulcer patients without and with complications by surgical treatment received in a retrospective population study using the National Health Insurance database in Taiwan.A cohort of 163,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
(41 reference statements)
0
7
0
1
Order By: Relevance
“…A recent study showed that vagotomy/drainage was superior to local oversewing in bleeding peptic ulcers that required emergency surgery . In addition, long‐term follow‐up studies showed that vagal nerve severance (vagotomy) decreased subsequent incidences of type 2 diabetes and ischemic heart disease in complicated peptic ulcer patients . These results indicate that persistent vagal hyperactivity may play an essential role in systemic homeostasis and there might be a role for vagal nerve severance in the management of patients with complicated peptic ulcer.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A recent study showed that vagotomy/drainage was superior to local oversewing in bleeding peptic ulcers that required emergency surgery . In addition, long‐term follow‐up studies showed that vagal nerve severance (vagotomy) decreased subsequent incidences of type 2 diabetes and ischemic heart disease in complicated peptic ulcer patients . These results indicate that persistent vagal hyperactivity may play an essential role in systemic homeostasis and there might be a role for vagal nerve severance in the management of patients with complicated peptic ulcer.…”
Section: Discussionmentioning
confidence: 98%
“…23,24 The likely explanations may include persistent vagal hyperactivity and increased systemic inflammatory status. 21,22 Other studies showed that vagal hyperactivity was related to the development of gastric stress ulceration, 16 and increased vagal parasympathetic tone was associated with peptic ulcer diseases in humans. 25,26 Those results indicate that there was an essential association between increased vagal tone and peptic ulcer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
ВведениеПо высокому уровню распространенности и экономическим затратам на лечение пептические язвы желудка (ЯЖ) и двенадцатиперстной кишки (ЯК) входят в число наиболее актуальных проблем современной медицины [1,2]. При этом сахарный диабет (СД) 2 типа является независимым фактором риска развития ЯЖ и ЯК [3-5], повышает частоту осложнений этих заболеваний [6], в частности, гастродуоденальных кровотечений [7][8][9]. Коморбидный СД увеличивает на 40-50 % смертность таких больных в течение первого месяца [10].
…”
unclassified